A construção da carreira dos ingressantes e o papel das instituições de ensino superior privada : um estudo de caso - Damião, Maria de Lurdes Zamora (2008)
This project is part of the Career Management area and deals with issues related to the criteria used for the career construction of beginning students of higher education. At the moment of decision making, young people are based on their desires and aspirations, as well as being pressured by cultural and social force. Do they only observe values ​​such as status, compensation and prestige? The question is permeated by the conception that the individual is a product and also a producer of culture. The relevance of this research is based on the search to understand the criteria used to build the professional path of university students, and what is the participation of higher education institutions in the process. The bibliographic research used for the construction of the theoretical platform, allows to deepen the knowledge on the subject, and serves as a base for the case study that involves beginning students of the business administration course and also a career management professional of a private higher education institution of São Paulo. (AU)